Complementarity of additionalities resulting from European Union funds: Perspective of the users of research infrastructures. Issue 2 (9th May 2022) - Hegerty, Scott W.; Kowalski, Arkadiusz M.; Lewandowska, Małgorzata S.
Abstract: The goal of this paper is to investigate the complementarity of three types of additionalities: input (growth of R&D investments), behavioral (changes in the internal processes of the entity), and output (leveraging social or private returns), occurring as the result of the 7th Framework Programme and Horizon 2020 European Union funds part INFRA. The empirical contribution is based on results of self‐created questionnaires conducted in 2016 with the use of CATI/CAWI on the unique sample of N  = 401 users of European Union research infrastructures from 32 countries. We create a Behavioral Additionality Index (BAI), which is a measurement tool that combines eight types (scale, scope, cognitive capacity, challenge, network, follow‐up, management, and acceleration) of behavioral additionalities. Based on the results of a logistic regression, we find that there is a positive relationship between input and behavioral additionality, as well as between behavioral additionality and output additionality. This last link, however, is not shown to be strengthened by input additionality. No significant differences in the level of the BAI were found between EU countries based on their level of innovativeness as measured by the Summary Innovation Index (SII), although we can observe that less developed EU countries, as well as on non‐EU countries, have higher BAI scores compared to developed ones. The overall results lead to the conclusion that the evaluation of public financial support has to be conducted not only for input, behavioral, and output additionalities separately, but must also take into account their complementarity—with its major focus on the behavioral aspects of this effect. RESUMEN: El objetivo de este artículo es investigar la complementariedad de tres tipos de adicionalidades: de entrada (crecimiento de las inversiones en I+D), de comportamiento (cambios en los procesos internos de la entidad) y de salida (apalancamiento de los rendimientos sociales o privados), que se producen como resultado del 7º Programa Marco y Horizonte 2020 fondos de la Unión Europea parte INFRA. La contribución empírica se basa en los resultados de cuestionarios de creación propia realizados en 2016 con el uso de CATI/CAWI en la muestra única de N = 401 usuarios de infraestructuras de investigación de la Unión Europea de 32 países. Creamos un Índice de Adicionalidad Conductual (BAI), que es una herramienta de medición que combina ocho tipos (escala, alcance, capacidad cognitiva, desafío, red, seguimiento, gestión y aceleración) de adicionalidades conductuales. Con base en los resultados de una regresión logística, encontramos que existe una relación positiva entre la adicionalidad de entrada y de comportamiento, así como entre la adicionalidad de comportamiento y la adicionalidad de salida. Sin embargo, no se muestra que este último vínculo se vea fortalecido por la adicionalidad de los insumos. No se encontraron diferencias significativas en el nivel del BAI entre los países de la UE en función de su nivel de innovación medido por el Summary Innovation Index (SII), aunque podemos observar que los países de la UE menos desarrollados, así como en los países de fuera de la UE, tienen puntajes BAI más altos en comparación con los desarrollados. Los resultados generales llevan a la conclusión de que la evaluación del apoyo financiero público debe llevarse a cabo no solo para las adicionalidades de entrada, comportamiento y salida por separado, sino que también debe tener en cuenta su complementariedad, centrándose principalmente en los aspectos de comportamiento de este efecto. 抽象的: 本文的目的是研究三種類型的附加性的互補性:投入(研發投資的增長)、行為(實體內部流程的變化)和產出(利用社會或私人回報)，作為結果發生歐盟第七框架計劃和地平線 2020 基金部分 INFRA。實證貢獻基於 2016 年使用 CATI / CAWI 對來自 32 個國家的 N = 401 個歐盟研究基礎設施用戶的獨特樣本進行的自行創建問卷的結果。我們創建了一個行為附加性指數(BAI)，它是一種測量工具，結合了八種類型(規模、範圍、認知能力、挑戰、網絡、跟進、管理和加速)的行為附加性。基於邏輯回歸的結果，我們發現輸入與行為額外性之間以及行為額外性與輸出額外性之間存在正相關關係。然而，這最後一個環節並沒有被輸入額外性所加強。根據總結創新指數 (SII) 衡量的創新水平，歐盟國家之間的 BAI 水平沒有顯著差異，儘管我們可以觀察到欠發達的歐盟國家以及非歐盟國家，與發達國家相比，BAI 得分更高。總體結果得出的結論是，公共財政支持的評估不僅必須分別針對投入、行為和產出額外性進行，而且還必須考慮它們的互補性——主要關注這種效應的行為方面.